A Literature Review: Effectiveness of Causal Learning Model in Improving Problem-Solving Ability - Wiwin Melia Utari; Aprilia Ika Dewi Anjani (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
The development of innovative learning models in the last decade demands a systematic evaluation of their effectiveness and implementation trends. This article presents a systematic literature review of 500 indexed publications (2016-2025) to analyze the development, impact, and research trends of causal learning models in improving learners' problem-solving skills, particularly in science learning. The analysis revealed a significant increase in publications related to this model, with a growth of 25% per year, although fluctuations occurred in certain periods. The dominance of research is in the form of journal articles (62 publications) with a primary focus on physics, with the Journal of Physics and Technology Education being the most productive source (17 articles, 122 citations). Empirical evidence is strong that the causal model, especially when combined with scaffolding, is effective in improving problem-solving skills (the top article received 36 citations). Conceptual mapping through VOSviewer showed close links between the model and critical thinking skills, conceptual understanding, and science learning. These findings strengthen the position of the causalytic model as a relevant learning strategy to address the challenges of 21st-century education, while highlighting the need for further research related to implementation across disciplines and educational contexts.